Model Problem Based Learning dalam Pembelajaran PAI di Sekolah, Madrasah dan Perguruan Tinggi - M. Iwan Saputra; Deddy Ramdhan (Mataram University, 2026)
Problem-Based Learning (PBL) is one of the instructional models considered effective in improving the quality of Islamic Religious Education (PAI) through a contextual problem-solving approach and student-centered learning. This article aims to comprehensively analyze the concepts, theoretical foundations, characteristics, syntax, implementation, advantages, and challenges of PBL in Islamic Religious Education at schools, madrasahs, and higher education institutions. This study employed a library research method by analyzing 26 literature sources consisting of 24 scientific journal articles, one book, and one supporting document relevant to the research topic. The collected data were analyzed using content analysis techniques. The findings indicate that PBL effectively enhances students’ critical thinking skills, learning motivation, communication skills, collaboration, and problem-solving abilities. At the school and madrasah levels, PBL has been shown to increase student engagement, improve understanding of Islamic Religious Education materials, and strengthen Islamic character through discussion and the resolution of real-life problems. At the higher education level, PBL contributes to the development of scientific reasoning, academic argumentation, and the integration of Islamic values in addressing contemporary social issues. However, the implementation of PBL still faces several challenges, including teacher readiness, differences in students’ abilities, limited instructional time, curriculum demands, and inadequate learning facilities and resources. Therefore, support from various stakeholders is required to ensure the optimal and sustainable implementation of PBL in Islamic Religious Education.